Rachel Friedman on Vulnerability and adaptation strategies among women in Ghanaian cocoa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Weathering change: Vulnerability and adaptation strategies among women in Ghanaian cocoa Presentation by Rachel Friedman from the University of Oxford at the seminar on Closing the gender gap in farming under climate change held 19 March 2015 in Paris Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action